Administrative liability of entities under Legislative Decree No. 231/2001 in the healthcare sector and residential care facilities (RSA): substantive aspects and recent case law (European journal of volunteering and community-based projects, 2025)
The paper analyzes the administrative liability of entities under Legislative Decree No. 231/2001 in the healthcare sector, with particular focus on Residential Care Facilities (RSA), contexts characterized by high organizational complexity and significant exposure to prevention-related risks. The author examines the evolution of the principle of “organizational fault,” the structure and effectiveness of Organizational, Management and Control Models (MOG), and the role of the Supervisory Body (OdV), in light of the most recent case law from lower and higher courts. The article highlights the need for RSAs to adopt truly operational and proportionate MOGs, integrated with occupational health and safety management systems (Legislative Decree No. 81/2008), based on thorough risk mapping, clear decision-making protocols, segregation of duties, and periodic effectiveness assessments. The analysis is particularly useful for social cooperatives, social enterprises, and other Third Sector entities managing RSAs, as it provides practical guidance for preventing administrative liability, strengthening governance and internal transparency, integrating quality and safety systems with the 231 compliance model, and reducing the risk of sanctions and disqualification measures. The best practices and case law trends discussed offer a strategic roadmap for enhancing regulatory and organizational compliance within welfare organizations operating in the fields of care and personal assistance.